The Brazilian system of financial activity safety in cyberspace and the current (in)applicability to the initial coin offerings (ICOs) and its virtual assets - SILVA, Susi Castro; MONTEIRO, Vitor Borges (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
New digital economy technologies, such as the initial coin offering (ICO) and its virtual assets, tokens and crypto-currencies, when coupled with software that anonymizes their transactions, potentiate the risks of virtual crime, money laundering, terrorist financing, and even cyber-attacks on the state financial system. Such cybernetic risks have demanded from governments the development of security systems for financial activity in cyberspace, involving cyber-defense mechanisms, oversight bodies, as well as normative devices to regulate, prevent and suppress cyber-attacks. In view of this scenario, the purpose of this research was to describe the Brazilian system of financial security in cyberspace, analyzing it in the face of the initial coin offering (ICO) phenomenon and its virtual assets, arriving at the conclusion that the current system is inapplicable to such a phenomenon.